(untitled) (Trabalho & Educação, 2017)
By bringing to the surface the field work carried out within the framework of researches based on dialectical historical materialism, the objective of this article is to identify threads that weave the work culture of the professional artisanal fishing in Mato Grosso’s Pantanal. Testimonials from fishermen and fisherwomen who accompany the researchers’ journey in the mainland and in the Paraguay River’s waters, contribute to answering some questions: How is the work process organized? How are the relations between humans and nature? And among human beings? How do they protect themselves from the dangers to which they are exposed? What are the customs and norms of coexistence in the camp? Is there any kind of associativity? Do each fisherman or fisherwoman fish for him or herself? To whom do the fruits of labor belong? After all, what is the purpose of fishing? Why do they want to participate in the formation of a cooperative? What work culture do fishermen and fisherwomen wish to materialize? As one of the many threads that weave the work culture of professional artisanal fishing in the Mato Grosso’s Pantanal, we indicate that the destructive logic of capital especially threatens the flora, fauna and way of life of traditional peoples and communities. As a research procedure, the text was discussed and conferred by the subjects of research, or rather, by the subjects of knowledge. ___ Ao trazer à superfície o trabalho de campo realizado no âmbito de pesquisas fundamentadas no materialismo histórico dialético, o objetivo do artigo é identificar fios que tecem a cultura do trabalho da pesca artesanal profissional no Pantanal Mato-Grossense. Depoimentos de pescadores e pescadoras que acompanham a viagem dos pesquisadores/as em terra-firme e nas águas do Rio Paraguai, contribuem para responder algumas perguntas: Como se dá a organização do processo de trabalho? Como são as relações entre seres humanos e natureza? E entre os seres humanos entre si? Como se protegem dos perigos a que estão expostos? No acampamento, quais os costumes e normas de convivência? Existe algum tipo de associatividade? Cada pescador/a pesca para si próprio? A quem pertencem os frutos do trabalho? Afinal, qual o objetivo da pesca? Por que querem participar da formação de uma cooperativa? Que cultura do trabalho os pescadores e pescadoras desejam materializar? Como um dos muitos fios que tecem a cultura do trabalho da pesca artesanal profissional no Pantanal Mato-Grossense, indicamos que a lógica destrutiva do capital ameaça sobremaneira a flora, a fauna e modo de vida dos povos e comunidades tradicionais. Como procedimento de pesquisa, o texto foi discutido e conferido pelos sujeitos da pesquisa, ou melhor, pelos sujeitos de saberes.